2020
DOI: 10.1155/2020/8375348
|View full text |Cite
|
Sign up to set email alerts
|

Predictive and Prognostic Role of PD-L1 in Urothelial Carcinoma Patients with Anti-PD-1/PD-L1 Therapy: A Systematic Review and Meta-Analysis

Abstract: Recently, checkpoint inhibition of the PD-1/PD-L1 axis has been shown to be therapeutically relevant in urothelial carcinoma (UC). To evaluate the predictive and prognostic value of PD-L1 on response and survival in UC patients after cystectomy, chemotherapy, or anti-PD-1/PD-L1 therapy, a systematic review of PubMed, Embase, Web of Science, and the Cochrane Library was performed. A total of 2154 patients from 14 published studies were included. In all UC patients after cystectomy, tumour cell (TC) PD-L1 expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Interestingly, the predictive value of PD-L1 expression significantly decreased in patients receiving anti-PD-L1 agents compared to those receiving anti-PD-1 agents. This trend has also been observed in carcinomas other than BTC (17,56,57). Further studies are warranted to verify whether the predictive value of PD-L1 expression differs depending on the target of ICIs (PD-1 vs. PD-L1) in cancer immunotherapy.…”
Section: Discussionmentioning
confidence: 68%
“…Interestingly, the predictive value of PD-L1 expression significantly decreased in patients receiving anti-PD-L1 agents compared to those receiving anti-PD-1 agents. This trend has also been observed in carcinomas other than BTC (17,56,57). Further studies are warranted to verify whether the predictive value of PD-L1 expression differs depending on the target of ICIs (PD-1 vs. PD-L1) in cancer immunotherapy.…”
Section: Discussionmentioning
confidence: 68%
“…In a separate analysis of patients with 1 of 10 prespecified advanced rare tumor types previously conducted through the Aarhus University pathology network, the prevalence of PD-L1 positivity varied from 13% in patients with neuroendocrine tumors (n=30) to 86% in patients with vulvar carcinoma (n=44) (26). Variation in prevalence of PD-L1 expression has also been reported in studies evaluating other tumor types, including NSCLC (25), gastric cancer (27)(28)(29), urothelial cancer (30), triple-negative breast cancer (31), and cervical carcinoma (32). Additionally, the relationship between PD-L1 positivity and clinical outcomes has also been found to vary between tumor types (29,(31)(32)(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 71%
“…17,18 Measurements of PD-L1 have been evaluated as a putative biomarker to inform the response to ICIs, but levels of expression are not always correlated with clinical responses. 19 Different studies found that between 14% and 29% of WT show tumor upregulation of PD-L1. [20][21][22] Zhang et al showed PD-L1 expression in 29% of 77 primary WT tumors, and 35% in metastatic WT.…”
Section: The Tumor Microenvironment In Wilms Tumormentioning
confidence: 99%
“…One of the most studied inhibitory pathways involves PD‐L1 and PD‐L2, B7 family members and ligands for the inhibitory receptor PD‐1 expressed by activated T cells 17,18 . Measurements of PD‐L1 have been evaluated as a putative biomarker to inform the response to ICIs, but levels of expression are not always correlated with clinical responses 19 . Different studies found that between 14% and 29% of WT show tumor upregulation of PD‐L1 20–22 .…”
Section: The Tumor Microenvironment In Wilms Tumormentioning
confidence: 99%